Physiological responses of growth and production of baby corn (Zea mays Saccharata L.) due to application of agricultural waste based compost and NPK fertilizer - Syamsir Pante Sukun; Amir Yassi; Ifayanti Ridwan Saleh (International Journal of Agriculture System, 2020)
A trial was conducted to study the physiological responses of baby corn to changes in soil fertility by application of organic and inorganic fertilizers.  The research was conducted at the Teaching Farm, Faculty of Agriculture, Universitas Hasanuddin from May to August 2020. The experiment was arranged based on a factorial randomized block design (RBD) with two factors repeated 3 times. The first factor is the dosage of green compost consisted of four levels, namely 0, 3, 4, and 5 tons ha-1. The second factor was the percentage of NPK fertilization from the recommendations consisted of four levels, namely NPK 100%, 75%, 50%, and 25%. The results show that the treatment of 4 ton ha-1 of green compost resulted in the highest absorption rate of CO2 (336.2 µmol CO2 mol-1) and the highest humidity level (68.8%). 100% NPK fertilizer treatment showed the highest CO2 absorption rate (338.1 µmol CO2 mol-1), the highest leaf photosynthesis rate (36.1 µmol CO2m-2s-1). The treatment of 5 ton ha-1 of green compost and 100% NPK fertilizer resulted in the lowest transpiration rate (0.20 liters m-2s-1). The treatment of 3 ton ha-1 green compost and 100% NPK fertilizer resulted in earlier flowering age (46.3 days) and heaviest ear weight (63.67 g). The treatment of 5 ton ha-1 green compost with 50% NPK fertilizer resulted in the longest ear length with husk (21.72 cm). Treatment of 4 ton ha-1 green compost with 100% NPK fertilization resulted in the longest ear length without husk (10.52 cm).